The Relationship between Degree of Differentiation with the Incidence of Lymphovascular Infiltration Triple Negative Breast Cancer in West Sumatera - Hidayat, Nur Latifah Alfaina; Yenita, Yenita; Khambri, Daan (Indonesian Journal of Cancer, 2023)
Background: The degree of differentiation and the incidence of lymphovascular infiltration in Triple Negative Breast Cancer (TNBC) are several determinants of the prognosis and survival of sufferers. This disease has a more aggressive clinical course than other breast cancer phenotypes. Targeted therapy has not been able to improve survival in TNBC patients. This study aims to analyze the relationship between the degree of differentiation and lymphovascular infiltration in Triple Negative Breast Cancer in West Sumatra. Methods: This is an observational analytic study with a cross-sectional approach. The number of study samples was 44 TNBC patients at the Ropanasuri Special Surgery Hospital, Ibnu Sina Islamic Hospital, and RSUP Dr. M. Djamil, Padang, in 2016–2021. The data studied were the degree of differentiation and lymphovascular infiltration from the results of anatomical pathology examination which were analyzed using the Chi Square test. Results: The most histopathological types in TNBC were Invasive Carcinoma Mammae of No Special Type (79,5%) with the most age range of patients over 60 years (43,2%). The majority of the degrees of differentiation found were grade II (75%), lymphovascular infiltration negative category (65,9%), and there was a significant relationship (p 0,001) between the degree of differentiation and lymphovascular infiltration in TNBC Conclusions: There was a relationship between the degree of differentiation and lymphovascular infiltration in TNBC, namely the higher the histopathological grade of cancer cells, the higher the probability of experiencing lymphovascular infiltration.